The role of high mobility group proteins in cellular senescence mechanisms - Chen, Jia; Li, Hongyu; Huang, Yongyin; Tang, Qiang (Frontiers in Aging, 2024)
Aging is a universal physiological phenomenon, and chronic age-related diseases have become one of the leading causes of human mortality, accounting for nearly half of all deaths. Studies have shown that reducing the incidence of these diseases can not only extend lifespan but also promote healthy aging. In recent years, the potential role of non-histone high-mobility group proteins (HMGs) in the regulation of aging and lifespan has attracted widespread attention. HMGs play critical roles in cellular senescence and associated diseases through various pathways, encompassing multi-layered mechanisms involving protein interactions, molecular regulation, and chromatin dynamics. This review provides a comprehensive analysis of the interactions between HMG family proteins and senescence-associated secretory phenotype (SASP), chromatin structure, and histone modifications, offering a deeper exploration of the pivotal functions and impacts of HMGs in the aging process. Furthermore, we summarize recent findings on the contributions of HMG proteins to aging and age-related diseases. HMG proteins not only regulate senescence-associated inflammation through modulating the SASP but also influence genomic stability and cell fate decisions via interactions with chromatin and histones. Targeting HMG proteins holds great potential in delaying the progression of aging and its associated diseases. This review aims to provide a systematic overview of HMG proteins’ roles in aging and to lay a solid foundation for future anti-aging drug development and therapeutic strategies. With the advancing understanding of the mechanisms by which HMGs regulate aging, developing therapeutic interventions targeting HMGs may emerge as a promising approach to extending lifespan and enhancing healthspan.